Processo de estampagem incremental do alumínio QQ-A-250/5 (2024-T3): análises por elementos finitos e experimentos - Marim, Tony Emerson (Universidade Federal de São Carlos, 2022)
The single point incremental forming method performed without die support is suitable for small batch and prototype product manufacturing due to the lower cost involved in its tooling acquisition, simplicity and flexibility of implementation. This concept makes the process viable for diverse applications in the medical, aerospace, and automotive industries, when largescale production of a product is not the priority but rather the individual analysis of a part or prototype construction and the manufacture of customized products. For frequent applications in industry the lack of some process information such as referential parameters of vertical displacements in the z-axis and velocity of displacements in the x and y axes makes it limited, they do not guarantee the appropriate guidelines that can ensure the use of incremental stamping on an industrial scale, which avoids wasting machine time and material resources in case of failure. To meet this need, the finite element method was used to perform the numerical analyses as an aid for a perception of the process particularities, applied in experiments that used a 0.4 mm thick plate of aluminum QQ-A-250/5 (2024-T3) as raw material and manufactured tooling composed of clamping brackets and dedicated tools, parameters were established based on limit diagrams that ensured the execution of manufacturing by incremental stamping of products with a good quality in surface finish. Using the computational model created and the information obtained regarding the final thickness of the material and its deformations after the conformation and after the simulations, parameters were obtained that inform the possibility of performing the operation. In the experiments performed, there was a guarantee of finalizing the depth determined when the tool with a 3 mm tip radius was used in three cases studied, being them with displacement in the z axis of 0.2 mm, 0.3 mm, and 0.4 mm. In the parts made with displacement in the z axis of 0.5 mm there was the appearance of rupture, which caused the interruption of the operation. In the cases where the tool with tip radius of 6 mm was used, all parts presented rupture, which compromised the performance of the operations. The use of the parameters that enabled the parts to reach the proposed depth, demonstrated by means of the failure prevention method applications in other profiles. All the data gathered were used to construct a method for analysis in the prediction of structural failures that may occur during the process, and by this method it was possible to predict the realization or not of the specific cases presented.
Incremental sheet metal forming process on QQ-A-250/5 aluminium alloy (2024-T3): finite element analyses and experiments
Keywords: Conformação de chapas; Detecção de falhas; Ponta única; Sheet metal forming; Failure detection; Single point; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; ENGENHARIAS::ENGENHARIA MECANICA